2005
DOI: 10.1021/es048019f
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Change of Copper in Fly Ash during de Novo Synthesis of Dioxins

Abstract: Although many researchers have reported that copper chloride is an important catalyst that generates relatively large amounts of dioxins in heat experiments involving model fly ash, details on the behavior of copper during the process are still unavailable. In this study, we used in situ XANES experiments involving one type of real fly ash, which originated from a municipal solid-waste incinerator (MSWI), and two fly ash models to investigate the behavior of copper in fly ash at temperatures that are suitable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 101 publications
(98 citation statements)
references
References 27 publications
6
91
0
Order By: Relevance
“…Thus, cupric chloride was partly and totally reduced (to CuCl) at 300 and 400 C, respectively. Analysis of Cl K-edge NEXAFS showed evidence that the previously reported reduction of cupric chloride 4,15 triggered chlorination of carbon by chlorine from copper. This also indicated that the chlorination potential was weakened by reduction to CuCl.…”
Section: Comparison Of Influences Among Heavy Metal Chloridesmentioning
confidence: 77%
“…Thus, cupric chloride was partly and totally reduced (to CuCl) at 300 and 400 C, respectively. Analysis of Cl K-edge NEXAFS showed evidence that the previously reported reduction of cupric chloride 4,15 triggered chlorination of carbon by chlorine from copper. This also indicated that the chlorination potential was weakened by reduction to CuCl.…”
Section: Comparison Of Influences Among Heavy Metal Chloridesmentioning
confidence: 77%
“…CBzs and PCBs do not contain oxygen in their structures. The generation of aromatic-Cls containing no oxygen was thought to be mainly influenced by the oxidative destruction of macromolecular carbon, which might be caused by gaseous oxygen and the catalytic role of cupric chloride (Takaoka et al, 2005;). Concentrations of ÎŁPCDFs and ÎŁPCBs from graphite at 400°C were 22 and 9 times higher, respectively, than that at 300°C.…”
Section: The Generation Of Pcdds Pcdfs Pcbs and Cbzsmentioning
confidence: 99%
“…According to earlier work, the Cu element (Table 1) determined by the elemental analysis is probably present as the chloride and oxide forms. 31) It is therefore possible that fine-particles of KCl and copper chlorides might react with C( ) to form C-O…”
Section: Possible Routes For De Novo Synthesis Of Organicmentioning
confidence: 99%